Reclaiming our Black bodies: reflections on a portrait of Sarah (Saartjie) Baartman and the destruction of Black bodies by the state - I. D. Mothoagae (Acta Theologica)
The parading of the nude body of Sarah Baartman by the British colonisers led England and France to racially categorise her as a subhuman. Her Black body was viewed as something that can be violated, exploited, destructed, penetrated, and subjugated to various inhumane conditions. According to Fanon, there is a world order that determines who fits where and how: “The colonial world is a world cut in two”. The militaristic response by the state to the people’s protest point to the fact that technology, the regimes, and the targets still remain. In this article, I will argue that the use of violence by the colonial, imperial system against Sarah Baartman (Black people) has its origins in colonialism and slavery. I maintain that there is a distinction between “a body” and “the Body”. The paper will use as basis the intersectionality theory. Conclusions will be drawn.